The Aryl Hydrocarbon Receptor Suppresses Chronic Smoke-Induced Pulmonary Inflammation - Guerrina, Necola; Traboulsi, Hussein; Eidelman, David H.; Baglole, Carolyn J. (Frontiers in Toxicology, 2021)
The aryl hydrocarbon receptor (AhR) is a ligand-activated transcription factor expressed in the lungs that is activated by numerous xenobiotic, endogenous and dietary ligands. Although historically the AhR is known for mediating the deleterious response to the environmental pollutant dioxin, emerging evidence supports a prominent role for the AhR in numerous biological process including inflammation. We have shown that the AhR suppresses pulmonary neutrophilia in response to acute cigarette smoke exposure. Whether the AhR can also prevent lung inflammation from chronic smoke exposure is not known but highly relevant, given that people smoke for decades. Using our preclinical smoke model, we report that exposure to chronic cigarette smoke for 8-weeks or 4 months significantly increased pulmonary inflammation, the response of which was greater in Ahr-/- mice. Notably, there was an increased number of multinucleated giant cells (MNGCs) in smoke-exposed Ahr-/- mice without a change in cytokine levels. These data support a protective role for the AhR against the deleterious effects of cigarette smoke, warranting continued investigation into its therapeutic potential for chronic lung diseases.